Myrothecium roridum tode ex fries un tuberculariaceo patogeno de Euphorbia lathyris L. y Lactuca sativa L. - Tuset, J.J.=700 1 Hinarejos, C.; Garcia, J.
(Es, En)
ilus., 8 ref.
Keywords: NECROSIS; PATOGENESIS; SINTOMAS; PLANTAS ORNAMENTALES; CITRUS; ESPAÑA; CHANCRO